2020
DOI: 10.1111/cas.14303
|View full text |Cite
|
Sign up to set email alerts
|

ARL4C is associated with initiation and progression of lung adenocarcinoma and represents a therapeutic target

Abstract: Lung adenocarcinoma is the most common histological type of lung cancer and is classified into adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA) and invasive adenocarcinoma (IA). Atypical adenomatous hyperplasia (AAH) lesions are possible precursors to adenocarcinoma. However, the mechanism underlying the stepwise continuum of lung adenocarcinoma is unclear. In this study, the involvement of ADP‐ribosylation factor (ARF)‐like (ARL) 4C (ARL4C), a member of the small GTP‐binding protein famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
10

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 41 publications
1
32
0
10
Order By: Relevance
“…In addition, evidence has shown that the identification of molecular biomarkers can provide prognostic value for LUADs ( Wang et al, 2019 ; Zhang, Zhang & Yu, 2019 ). For example, high ARL4C expression is an essential prognostic factor in LUAD ( Kimura et al, 2020 ). However, a single gene biomarker is insufficient to produce comprehensive predictive effects and immune prognostic models were proposed for LUADs recently ( Luo et al, 2020 ; Yang et al, 2019 ; Yue, Ma & Zhou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence has shown that the identification of molecular biomarkers can provide prognostic value for LUADs ( Wang et al, 2019 ; Zhang, Zhang & Yu, 2019 ). For example, high ARL4C expression is an essential prognostic factor in LUAD ( Kimura et al, 2020 ). However, a single gene biomarker is insufficient to produce comprehensive predictive effects and immune prognostic models were proposed for LUADs recently ( Luo et al, 2020 ; Yang et al, 2019 ; Yue, Ma & Zhou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…positive for ARL4C and additionally another biomarker, identi ed patients likely to be dead within 5 years. These results indicate that ARL4C may contributes to more aggressive behavior of the tumor including a possibility of metastasis, as demonstrated that high expression of ARL4C in lung, liver, and colorectal cancers was an independent indicator of relapse [23,24]. The other three biomarkers may promote the progression of metastatic tumors.…”
Section: Discussionmentioning
confidence: 54%
“…Conversely, by setting the cut-off point to 11, the high-(> 11) scored group, i.e., positive for ARL4C and additionally another biomarker, identified patients likely to be dead within 5 years. These results indicate that ARL4C may contributes to more aggressive behavior of the tumor including a possibility of metastasis, as demonstrated that high expression of ARL4C in lung, liver, and colorectal cancers was an independent indicator of relapse [ 23 , 24 ]. The other three biomarkers may promote the progression of metastatic tumors.…”
Section: Discussionmentioning
confidence: 89%
“…Shorter survival from the time of diagnosis of metastasis is seen in cases with higher expression levels of ARL4C (log-rank test, a p = 0.006, chi-square value = 7.53), SOD2 (log-rank test, c p = 0.011, chi-square value = 6.54), and STEAP3 (log-rank test, d p = 0.003, chi-square value = 8.95). e The patients were divided into high-and low-risk scored groups under our model of risk stratification by setting the cut-off value to 17 points; the high-(> 17) risk score predicted likely demise within 2 years more accurately than each individual biomarker (log-rank test, e p < 0.001, chi-square value = 21.66) Compared to the highest-risk scored group, high SOD2 expression could accurately predict those patients likely to be dead within 30 months of initiation of MTT a possibility of metastasis, as demonstrated that high expression of ARL4C in lung, liver, and colorectal cancers was an independent indicator of relapse [23,24]. The other three biomarkers may promote the progression of metastatic tumors.…”
Section: Discussionmentioning
confidence: 97%